Penerapan landasan psikologis dalam bimbingan dan konseling di sd muhammadiyah labschool umtas - Rosa Ansori Putri ansori; Pipih Holilah; Liyan Mulyani; Faisa Kamilah; Hilma Aulia; Amanda Aulia (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to determine the influence of psychological foundations in guidance and counseling regarding the meaning, function, and basic psychological principles in counseling guidance services at SD MUHAMMADIYAH. This study uses an interview method with elementary school teachers. Based on the results of research 1). The school uses the Independent Curriculum for Indonesian subjects in grade 1 of elementary school, the school does not have a BK teacher, so the homeroom teacher concurrently serves as a BK teacher. Psychological problems that students often face, especially students with special needs (ADHD). 2) an approach that is carried out through direct communication with parents to understand the student’s condition. Problem identification is carried out through open communication between teachers and students.